Nonmotor and extracerebellar features in Machado‐Joseph disease: A review. Issue 9 (17th June 2013) - Pedroso, José Luiz; França, Marcondes C.; Braga‐Neto, Pedro; D'Abreu, Anelyssa; Saraiva‐Pereira, Maria Luiza; Saute, Jonas A.; Teive, Hélio A.; Caramelli, Paulo; Jardim, Laura Bannach; Lopes‐Cendes, Iscia; Barsottini, Orlando Graziani P.
ABSTRACT Spinocerebellar ataxia type 3 or Machado‐Joseph disease is the most common spinocerebellar ataxia worldwide, and the high frequency of nonmotor manifestations in Machado‐Joseph disease demonstrates how variable is the clinical expression of this single genetic entity. Anatomical, physiological, clinical, and functional neuroimaging data reinforce the idea of a degenerative process involving extracerebellar regions of the nervous system in Machado‐Joseph disease. Brain imaging and neuropathologic studies have revealed atrophy of the pons, basal ganglia, midbrain, medulla oblongata, multiple cranial nerve nuclei, and thalamus and of the frontal, parietal, temporal, occipital, and limbic lobes. This review provides relevant information about nonmotor manifestations and extracerebellar symptoms in Machado‐Joseph disease. The main nonmotor manifestations of Machado‐Joseph disease described in previous data and discussed in this article are: sleep disorders, cognitive and affective disturbances, psychiatric symptoms, olfactory dysfunction, peripheral neuropathy, pain, cramps, fatigue, nutritional problems, and dysautonomia. In addition, we conducted a brief discussion of noncerebellar motor manifestations, highlighting movement disorders. © 2013 Movement Disorder Society